Rhabdomyosarcoma of the Gluteus Maximus - Case Report, Review of Literature and Emerging Therapeutic Targets - Meshram, Gulab Girish; Kaur, Neeraj; Hura, Singh Kanwaljeet (Klinicka onkologie, 2019)
BACKGROUND: Rhabdomyosarcoma is an uncommon mesodermal cancer, which predominantly affects the young population. Common sites of primary disease include the head and neck region, genitourinary tract and the extremities. Less than 25% of the cases of rhabdomyosarcoma are metastatic at presentation. Embryonal and alveolar are the most common histological subtypes of rhabdomyosarcoma. Literature about rhabdomyosarcoma located in the gluteal region is sparse. CASE: We present a case of a 3-year-old child with alveolar rhabdomyosarcoma arising from the gluteal region. The metastatic workup was negative. We determined the tumour to be of intermediate risk and managed the patient with systemic chemotherapy consisting of cycles of vincristine, actinomycin D and cyclophosphamide, along with local treatment (wide-margin excision and radiotherapy). No recurrence was observed in the follow-up period. CONCLUSION: Management of alveolar rhabdomyosarcoma of the gluteus maximus requires a multipronged approach consisting of systemic chemotherapy, local surgery and radiotherapy. Long-term surveillance is imperative in children for early identification and management of relapses and treatment-related adverse effects. Several biological agents and small-molecule inhibitors targeting the signalling and growth pathways of rhabdomyosarcoma are in the pipeline, which hold promise for personalised therapy in the future. However, due to the rarity and molecular heterogenicity of the tumour, integrating these novel agents with the existing therapy would be a challenge.
Keywords: kombinovaná terapie; Rhabdomyosarcoma, Alveolar; Buttocks; Vincristine; Humans; Dactinomycin; hýždě; protokoly protinádorové kombinované chemoterapie; lidé; daktinomycin; buttocks; předškolní dítě; vinkristin; Antineoplastic Combined Chemotherapy Protocols; Cyclophosphamide; chemotherapy; rhabdomyosarcoma; Combined Modality Therapy; Child, Preschool; cyklofosfamid; alveolární rhabdomyosarkom